Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia Dan Upah Minimum Provinsi Terhadap Ketimpangan Distribusi Pendapatan Provinsi-Provinsi Di Pulau Jawa Tahun 2011-2020 - Ivanovi Sulistyaningrum, Berliana; Bhinadi, S.E, M.Si, Dr. Ardito; Dwi Astuti, S.E, M.Si, Rini (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Equitable distribution and improvement of welfare are the goals of economic development in a country. High economic growth must always be accompanied by an even distribution of income, otherwise it will cause new problems, that is income distribution of income. This study aims to analyze the effect of economic growth, the Human Development Index (HDI) and the Provincial Minimum Wage (PMW) on the income distribution inequality in the provinces in Java in 2011-2020. This research uses quantitative methods. The type of data used is secondary sourced from the Central Statistics Agency. The data used is panel data from six provinces in Java. The analytical tool used is the panel data regression method using Stata 16 software. The results of the study state that economic growth has no effect on inequality in income distribution. The Human Development Index (HDI) has no negative and significant effect on income distribution inequality and the Provincial Minimum Wage (PMW) has a negative effect on income distribution inequality.